Utilizing the Welch-Powell Algorithm and the IDO (Incident Degree Ordering) Algorithm in Traffic Light Settings - Latif, Sintia Abdul; Nurwan; K. Hasan, Isran; Achmad, Novianita; Wungguli, Djihad; Nashar, La Ode (Universitas PGRI Palembang, 2024)
The road junction needs some help with the timing of traffic lights. One method for optimizing crossroads traffic light settings is using a graph approach that applies a vertex coloring algorithm. The Welch-Powell and IDO (Incident Degree Ordering) algorithms are used to solve this problem. This case study covers two crossroads, namely: the crossroads of Prof. Dr. H.B. Jassin, Jenderal Sudirman Street, and the crossroads of Prof. Dr. H.B. Jassin, Palma, Sarini Abdullah Street. The result showed that the Welch-Powell and IDO algorithms used for vertex coloring produced XG=3 chromatic numbers for Prof. Dr. H.B Jassin, Jenderal Sudirman Street, and XG=4 for Prof. Dr. H.B Jassin, Palma, and Sarini Abdullah Street. New data shows that green-light efficiency increases by 23.85% and red-light efficiency decreases by 19.26% for crossroads of three, and new data at crossroads of four shows that data in the field is more effective than new data.